Investigating the impact of internship courses and entrepreneurship principles on the entrepreneurial intention of agricultural students - Baluchi, Nazanin (2020)
The purpose of this study was to investigate the impact of internship courses and entrepreneurship fundamentals on the entrepreneurial intention of students of applied science educational centers in western Iran. This research is in terms of degree of control and degree of control, field and in terms of method of obtaining facts and data is survey type and in terms of data collection, is causal-correlational. The statistical population of this study was 388 students of agricultural and undergraduate courses in Applied Science Education Centers in four western provinces of Iran (Ilam, Kermanshah, Lorestan and Kurdistan). Since the list of students who have completed internship and entrepreneurship courses is available, so the sample was selected as a whole sample and finally 250 questionnaires were returned. The data collection tool was a researcher-made questionnaire whose content validity was confirmed by a panel of experts and its reliability was confirmed by Cronbach's alpha. The results of structural equation modeling (SEM) using Amos24 software showed that based on the model, in the standard case, the effect of the internship period on attitude towards behavior 0.08, perceived behavioral control 0.05 and subjective norms 19 Is 0 which is a weak to medium effect. Also, in the standard case, the effect of entrepreneurship fundamentals on attitudes toward behavior is 0.56, perceived behavioral control is 0.56 and subjective norms is 0.45 which is a moderate to strong effect.